Dynamic Control of Photoresponse in ZnO-Based Thin-Film Transistors in the Visible Spectrum - Levent E. Aygun; Feyza B. Oruc; Fatih B. Atar; Ali K. Okyay (IEEE Photonics Journal)
We present ZnO-channel thin-film transistors with actively tunable photocurrent in the visible spectrum, although ZnO band edge is in the ultraviolet. ZnO channel is deposited by atomic layer deposition technique at a low temperature (80 <tex Notation="TeX">$^{°}\hbox{C}$</tex> ), which is known to introduce deep level traps within the forbidden band of ZnO. The gate bias dynamically modifies the occupancy probability of these trap states by controlling the depletion region in the ZnO channel. Unoccupied trap states enable the absorption of the photons with lower energies than the bandgap of ZnO. Photoresponse to visible light is controlled by the applied voltage bias at the gate terminal.